Factors Affecting Achievement Employee Work In Tlogosari District Office Bondowoso - Zulfikar Ardiansyah; Agustin Hari Prastyowati; Suwignyo Widagdo (ABM: International Journal of Administration, Business and Management, 2021)
In order to increase employee performance to achieve the vision, mission and goals to the maximum, work performance assessment, work motivation and the creation of a conducive work environment must be conditioned by a leader. The purposes of this study were (1) to determine and analyze the significant simultaneously (simultaneous) between the variables of assessment material, intrinsic motivation, extrinsic motivation, and work environment on employee performance at the Tlogosari Bondowoso District Office, and (2) to determine and analyze partial effect between the variables of intrinsic motivation assessment material, extrinsic motivation, and work environment on employee performance at the Tlogosari Bondowoso District Office. The population in this study were all 33 employees of the Tlogosari District office , Bondowoso Regency . The data collected was measured using a Likert scale. The results showed that (1) of the four independent variables (assessment material, intrinsic motivation, extrinsic motivation and work environment) turned out to have an effect together (simultaneously) 43 . 00 percent of the work performance of the employees of the Tlogosari District Office, Bondowoso Regency. These findings indicate that to improve the work performance of the employees of the Tlogosari District Office, Bondowoso Regency, it is necessary to pay attention to the variables of assessment material, intrinsic motivation, extrinsic motivation and work environment. (2) of the four independent variables (assessment material, intrinsic motivation, extrinsic motivation and work environment), it turns out that partially have a very significant and positive effect on employee work performance at the Tlogosari District Office, Bondowoso Regency. Based on the results, researchers can provide advice, among others: (1) variable material appraisal (X 1 ), intrinsic motivation (X 2 ), extrinsic motivation (X 3 ), and the work environment (X 4 ) together have significant or significant influence on work performance. It is hoped that it will continue to be considered in order to maintain and improve the work performance of the employees of the Tlogosari District Office, Bondowoso Regency sequentially, namely the assessment material (X 1 ), intrinsic motivation (X 2 ), extrinsic motivation (X 3 ), and work environment (X 4 ) is expected to remain a leadership policy in an effort to improve employee performance. Keywords : Assessment Material, Intrinsic Motivation, Extrinsic Motivation, Work Environment, Work Achievement